2020
DOI: 10.1097/mnm.0000000000001154
|View full text |Cite
|
Sign up to set email alerts
|

Early detection of progressive disease using thyroglobulin doubling-time in metastatic differentiated thyroid carcinoma treated with radioactive iodine

Abstract: Objective Detectable serum thyroglobulin (Tg) in patients with differentiated thyroid carcinoma (DTC) after total thyroidectomy indicates progression of the disease. Thyroglobulin doubling-time (TgDT) is a powerful prognostic predictor in patients with DTC. We aimed to evaluate the value of the dynamic TgDT for early detection of progressive disease (PD) in the patients of metastatic DTC with 131I radioactive iodine (RAI) therapy. Methods We retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…About survival, we demonstrated that Tg before PET, PET results and ATA class risk were independent prognostic variables, while other Tg kinetics factors were not significantly related to survival. This evidence is partially in contrast with previous studies [14][15][16]20], probably due to the heterogeneity of population investigated and the different timing of Tg kinetics measurement. Moreover, the heterogeneity of DTC evolution and disease status at time of PET/CT may influence this kind of evaluation.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…About survival, we demonstrated that Tg before PET, PET results and ATA class risk were independent prognostic variables, while other Tg kinetics factors were not significantly related to survival. This evidence is partially in contrast with previous studies [14][15][16]20], probably due to the heterogeneity of population investigated and the different timing of Tg kinetics measurement. Moreover, the heterogeneity of DTC evolution and disease status at time of PET/CT may influence this kind of evaluation.…”
Section: Discussioncontrasting
confidence: 99%
“…Some authors [14][15][16] demonstrated that TgDT was significantly associated with disease specific survival and their prognostic value was better than conventional variables, such as age and primary's size. These authors underlined the Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors stressed the point about exponential changes in volume of growing tumors, which is most amenable to measurements with doubling time rather than the alternative of velocity (best for linear changes). Subsequent papers [ 20 , 21 ] confirmed these findings. Interestingly, TgV also showed prognostic value for predicting DTC recurrence, demonstrating a specificity of 94.4% and a sensitivity of 83.3% at the threshold of 0.3 ng/mL/year.…”
Section: Discussionmentioning
confidence: 71%
“…Nevertheless, we did not find a significant difference in the Tg levels (either stimulated or suppressed) among the patients who developed structural recurrence compared to patients who remained BIR or who reverted to NED. Of note, only a small subset of patients had enough serial Tg measurements available to address the doubling time as a possible predictor [11][12][13]. Applying dynamic risk stratification based on post treatment Tg levels only revealed that a minority of BIR patients will eventually develop a structural disease, and the Tg trend was found to be useful in identifying those patients [14,15].…”
Section: Tg Levels and Timing Definitionmentioning
confidence: 99%